2010
DOI: 10.1029/2009ja015050
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical and magnetic field time constants for Titan's ionosphere: Empirical estimates and comparisons with Venus

Abstract: Plasma in Titan's ionosphere flows in response to forcing from thermal pressure gradients, magnetic forces, gravity, and ion‐neutral collisions. This paper takes an empirical approach to the ionospheric dynamics by using data from Cassini instruments to estimate pressures, flow speeds, and time constants on the dayside and nightside. The plasma flow speed relative to the neutral gas speed is approximately 1 m s−1 near an altitude of 1000 km and 200 m s−1 at 1500 km. For comparison, the thermospheric neutral wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 57 publications
(132 reference statements)
6
47
0
Order By: Relevance
“…Although the present model does not reproduce the detailed variations in the magnetic field observations very effectively, the analysis of the model results is still useful for understanding the ionospheric dynamics at Titan. Unlike Venus, the substantial thickness of Titan's ionosphere and potential horizontal forces and horizontal plasma motion, especially in the region below the exobase ($1500 km) -as suggested by Cravens et al (2010), Müller-Wodarg et al (2008), and Cui et al (2009) -imply that modeling Titan's interaction and ionosphere requires a 3D treatment. Therefore, 3D numerical experiments such as the one presented here are necessary for analysis of Titan's ionosphere.…”
Section: Simulation Results and Comparisons With Observationsmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the present model does not reproduce the detailed variations in the magnetic field observations very effectively, the analysis of the model results is still useful for understanding the ionospheric dynamics at Titan. Unlike Venus, the substantial thickness of Titan's ionosphere and potential horizontal forces and horizontal plasma motion, especially in the region below the exobase ($1500 km) -as suggested by Cravens et al (2010), Müller-Wodarg et al (2008), and Cui et al (2009) -imply that modeling Titan's interaction and ionosphere requires a 3D treatment. Therefore, 3D numerical experiments such as the one presented here are necessary for analysis of Titan's ionosphere.…”
Section: Simulation Results and Comparisons With Observationsmentioning
confidence: 97%
“…This study is also complementary to recent work by Cravens et al (2010), where an empirical approach is taken to explore the ionospheric dynamics in Titan's ionosphere. In their work, estimates for thermal and magnetic pressures, plasma flow speeds and time constants of different ionospheric processes are obtained by using Cassini data for the T17, T18, and T5 flybys and by estimating pressure gradients using characteristic length-scales.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Localized heating of the atmosphere by ion precipitation may have a significant impact on the neutral density profiles. In addition it has been suggested that the neutral winds may have an influence on how the magnetic field slides around Titan (Cravens et al, 2010). These are just some of the outstanding issues that remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%